Interpretacja mesjańska wyrażenia „słońce sprawiedliwości” (Ml 3,20) - Dogondke, Dariusz (Verbum Vitae, 2014)
Christian tradition reads the words of the prophet Malachi on „the sun of righteousness” (Mal 3:20) as Messianic, calling Jesus Christ the sun of righteousness. This paper is an attempt to justify this belief in the context of the Old Testament, especially of the Book of Malachi. Indeed, the Messianic nature of this expression is indicated by the closest context, in which the image of rising sun has been contrasted with the image of the lack of root and branch. The total destruction of „root and branch” means no messianic hope for the wicked (Mal 3:19), but for the Godfearing the rising of the sun of righteousness is prelude to the fulfillment of this hope, about which the prophet Malachi convinces us also in these words: the sun of righteousness will rise „with its heeling rays” (Mal 3:20). On the basis of the Old Testament exegesis, the Messianic interpretation of the expression „the sun of righteousness” is fully justified.